International trends of orthodontic publications: A bibliometric observational study of the last decade (2011-2020) - Nabeel ALMOTAIRY (Dental Press Editora, 2023)
ABSTRACT Introduction: The number of published orthodontic studies has increased considerably over the past ten years. Objective: To analyze the bibliometric data of international orthodontic studies included in orthodontic journals encompassed by the Scopus database between 2011 and 2020, as well as to undertake data comparison between the period 2010-2015 and the period 2016-2020. Materials and methods: A retrospective search was conducted on 14 orthodontic journals included in the Scopus database from 2011 to 2020. Studies of both primary and secondary types were targeted by the search. The yearly number of studies published in the 14 journals, and the first 20 countries, institutions and their type (public/private), and authors, respectively, regarding publication volume, were presented. Results: Over the past ten years, the number of publications in the chosen journals reached 9200, where the American Journal of Orthodontics and Dentofacial Orthopedics and Angle Orthodontist topped the journal list, with 22% and 12% of the publications, respectively. Furthermore, the orthodontic publication volume showed a declining trend by the end of the decade (-9%), where academic/public institutions produced most of the orthodontic studies, and the US (20%), Brazil (17%), and South Korea (8%) topped the countries with the most orthodontic studies. A comparison of the two halves of the decade revealed that orthodontic research exhibited an increasing trend in developing nations, especially Egypt (104%), Saudi Arabia (88%), and Iran (83%). Conclusion: The orthodontic studies published in the chosen journals over the past ten years showed a dynamic change in yearly publication and ranking of countries, institutions, and authors.